Power Allocation for 5G Mobile Multiuser Cooperative Networks - Yin, Fagen; Du, Wencai (Journal of Advanced Transportation, 2021)
With the fifth generation (5G) communication technology, the mobile multiuser networks have developed rapidly. In this paper, the performance analysis of mobile multiuser networks which utilize decode-and-forward (DF) relaying is considered. We derive novel outage probability (OP) expressions. To improve the OP performance, we study the power allocation optimization problem. To solve the optimization problem, we propose an intelligent power allocation optimization algorithm based on grey wolf optimization (GWO). We compare the proposed GWO approach with three existing algorithms. The experimental results reveal that the proposed GWO algorithm can achieve a smaller OP, thus improving system efficiency. Also, compared with other channel models, the OP values of the 2-Rayleigh model are increased by 81.2% and 66.6%, respectively.

Learning dynamics of kernel-based deep neural networks in manifolds - Wu, Wei; Jing, Xiaoyuan; Du, Wencai; Chen, Guoliang (Science China Information Sciences, 2021)

A Fast Lightweight Based Deep Fusion Learning for Detecting Macula Fovea Using Ultra-Widefield Fundus Images - Wang, Han; Yang, Jie; Wu, Yaoyang; Du, Wencai; Fong, Simon; Duan, Yutong; Yao, Xiaoping; Zhou, Xiaoshu; Li, Qingqian; Lin, Chen; Liu, Jiang; Huang, Lina; et al. (MATHEMATICS & COMPUTER SCIENCE, 2021)
Macula fovea detection is a crucial prerequisite towards screening and diagnosing macular diseases. Without early detection and proper treatment, any abnormality involving the macula may lead to blindness. However, with the ophthalmologist shortage and time-consuming artificial evaluation, neither accuracy nor effectiveness of the diagnose process could be guaranteed. In this project, we proposed a deep learning approach on ultra-widefield fundus (UWF) images for macula fovea detection. This study collected 2300 ultra-widefield fundus images from Shenzhen Aier Eye Hospital in China. Methods based on U-shape network (Unet) and Fully Convolutional Networks (FCN) are implemented on 1800 (before amplifying process) training fundus images, 400 (before amplifying process) validation images and 100 test images. Three professional ophthalmologists were invited to mark the fovea. A method from the anatomy perspective is investigated. This approach is derived from the spatial relationship between macula fovea and optic disc center in UWF. A set of parameters of this method is set based on the experience of ophthalmologists and verified to be effective. Results are measured by calculating the Euclidean distance between proposed approaches and the accurate grounded standard, which is detected by Ultra-widefield swept-source optical coherence tomograph (UWF-OCT) approach. Through a comparation of proposed methods, we conclude that, deep learning approach of Unet outperformed other methods on macula fovea detection tasks, by which outcomes obtained are comparable to grounded standard method.

Key Issues for Digital Factory Designing and Planning: A Survey - Wang, Han; Du, Wencai; Li, Shaobin (Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing, 2022)
Digital Factory (DF) planning is the key of intelligent factory construction, where intelligent production technologies of big data analysis, cloud computing, blockchain, Internet of Things, artificial intelligence, 5G, Time Sensitive Network (TSN), Digital Twin (DT), additive manufacturing are included. By applying the modern techniques, DF performs great advantages on the aspects of product lifecycle management, enterprise resource planning, operation management, supply chain management, real-time database construction, advanced process control, as well as the new technologies of distributed control system and fieldbus control system. This article delivers a review of key issues of DF top-level design and planning from the aspects of networking, precision, automation and digitalization. Solutions are explored based on 5G, TSN and DT advanced technologies, literately and practically. Additionally, the article describes the method and application of efficient big data comprehensive solution. Therefore, this study contributes valuable decision-making support for DF applications.
Keywords: 5G; Big data comprehensive solution; Digital Factory; Digital twin; Time Sensitive Network

Quality Detection Method for Controller Process Based on Mask R-CNN Network Model - Ma, Xinlei; Chen, Yanyu; Li, Shaobin; Du, Wencai; Tan, Zehan; Li, Qinggu; Ma, Yaqi; Deng, Haiyan (2021 8th International Conference on Computational Science/Intelligence and Applied Informatics (CSII), 2021)

Foreword - Ma, J.; Du, W.; Lu, W. (Studies in Computational Intelligence, 2023)

Message from Program Chairs - Ma, J.; Du, W.; Lu, W. (Proceedings - 2022 IEEE/ACIS 22nd International Conference on Computer and Information Science, ICIS 2022, 2022)

A Comprehensive Review of Investor Sentiment Analysis in Stock Price Forecasting - Ma, Huawen; Ma, Jixin; Wang, Han; Li, Pengsheng; Du, Wencai (2021 IEEE/ACIS 20th International Fall Conference on Computer and Information Science (ICIS Fall), 2021)
Sentiment analysis technologies have a strong impact on financial markets. In recent years there has been increasing interest in analyzing the sentiment of investors. The objective of this paper is to evaluate the current state of the art and synthesize the published literature related to the financial sentiment analysis, especially in investor sentiment for prediction of stock price. Starting from this overview the paper provides answers to the questions about how and to what extent research on investor sentiment analysis and stock price trend forecasting in the financial markets has developed and which tools are used for these purposes remains largely unexplored. This paper represents the comprehensive literature-based study on the fields of the investors sentiment analytics and machine learning applied to analyzing the sentiment of investors and its influencing stock market and predicting stock price.
Keywords: Analytical models; Information science; Investor sentiment analysis; Machine learning; Market research; Predictive models; Reliability; Sentiment analysis; Social media; Stock price trend forecasting; Tools

A Model of Integrating Bert and BiGRU+ Attention Dual-channel Mechanism for Investor Sentiment Analysis of Stock Price Forecast - Ma, Huawei; Ma, Jixin; Liang, Shengbin; Du, Wencai (2022 IEEE/ACIS 23rd International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD), 2022)

A Deep Neural Network Based on Circular Representation for Target Detection - Lin, Cong; Chen, Zhoujian; Huang, Yiquan; Jiang, Haoyu; Du, Wencai; Chen, Qiong (Journal of Sensors, 2022)
Convolutional neural network (CNN) model based on deep learning has excellent performance for target detection. However, the detection effect is poor when the object is circular or tubular because most of the existing object detection methods are based on the traditional rectangular box to detect and recognize objects. To solve the problem, we propose the circular representation structure and RepVGG module on the basis of CenterNet and expand the network prediction structure, thus proposing a high-precision and high-efficiency lightweight circular object detection method RebarDet. Specifically, circular tubular type objects will be optimized by replacing the traditional rectangular box with a circular box. Second, we improve the resolution of the network feature map and the upper limit of the number of objects detected in a single detect to achieve the expansion of the network prediction structure, optimized for the dense phenomenon that often occurs in circular tubular objects. Finally, the multibranch topology of RepVGG is introduced to sum the feature information extracted by different convolution modules, which improves the ability of the convolution module to extract information. We conducted extensive experiments on rebar datasets and used AB-Score as a new evaluation method to evaluate RebarDet. The experimental results show that RebarDet can achieve a detection accuracy of up to 0.8114 and a model inference speed of 6.9 fps while maintaining a moderate amount of parameters, which is superior to other mainstream object detection models and verifies the effectiveness of our proposed method. At the same time, RebarDet’s high precision detection of round tubular objects facilitates enterprise intelligent manufacturing processes.

A medical text classification approach with ZEN and capsule network - Liang, Shengbin; Sun, Fuqi; Sun, Haoran; Chen, Tingting; Du, Wencai (The Journal of Supercomputing, 2023)
Text classification is an important topic in natural language processing, with the development of social network, many question-and-answer pairs regarding health-care and medicine flood social platforms. It is of great social value to mine and classify medical text and provide targeted medical services for patients. The existing algorithms of text classification can deal with simple semantic text, especially in the field of Chinese medical text, the text structure is complex and includes a large number of medical nomenclature and professional terms, which are difficult for patients to understand. We propose a Chinese medical text classification model using a BERT-based Chinese text encoder by N-gram representations (ZEN) and capsule network, which represent feature uses the ZEN model and extract the features by capsule network, we also design a N-gram medical dictionary to enhance medical text representation and feature extraction. The experimental results show that the precision, recall and F1-score of our model are improved by 10.25%, 11.13% and 12.29%, respectively, compared with the baseline models in average, which proves that our model has better performance.
Keywords: Capsule network; Medical text classification; Text mining; ZEN model

An Improved Dual-Channel Deep Q-Network Model for Tourism Recommendation - Liang, Shengbin; Jin, Jiangyong; Ren, Jia; Du, Wencai; Qu, Shenming (Big Data, 2023)
Keywords: context-aware; deep reinforcement learning; dual-channel; tourism recommendation

A Multi-Channel Text Sentiment Analysis Model Integrating Pre-training Mechanism - Liang, Shengbin; Jin, Jiangyong; Du, Wencai; Qu, Shenming (Information Technology and Control, 2023)
The number of tourist attractions reviews, travel notes and other texts has grown exponentially in the Internet age. Effectively mining users’ potential opinions and emotions on tourist attractions, and helping to provide users with better recommendation services, which is of great practical significance. This paper proposes a multi-channel neural network model called Pre-BiLSTM combined with a pre-training mechanism. The model uses a combination of coarse and fine- granularity strategies to extract the features of text information such as reviews and travel notes to improve the performance of text sentiment analysis. First, we construct three channels and use the improved BERT and skip-gram methods with negative sampling to vectorize the word-level and vocabulary-level text, respectively, so as to obtain more abundant textual information. Second, we use the pre-training mechanism of BERT to generate deep bidirectional language representation relationships. Third, the vectors of the three channels are input into the BiLSTM network in parallel to extract global and local features. Finally, the model fuses the text features of the three channels and classifies them using SoftMax classifier. Furthermore, numerical experiments are conducted to demonstrate that Pre-BiLSTM outperforms the baselines by 6.27%, 12.83% and 18.12% in average in terms of accuracy, precision and F1-score.
Keywords: Pre-training mechanism

An improved ant colony optimization algorithm based on context for tourism route planning - Liang, Shengbin; Jiao, Tongtong; Du, Wencai; Qu, Shenming (PLOS ONE, 2021)
To solve the problem of one-sided pursuit of the shortest distance but ignoring the tourist experience in the process of tourism route planning, an improved ant colony optimization algorithm is proposed for tourism route planning. Contextual information of scenic spots significantly effect people’s choice of tourism destination, so the pheromone update strategy is combined with the contextual information such as weather and comfort degree of the scenic spot in the process of searching the global optimal route, so that the pheromone update tends to the path suitable for tourists. At the same time, in order to avoid falling into local optimization, the sub-path support degree is introduced. The experimental results show that the optimized tourism route has greatly improved the tourist experience, the route distance is shortened by 20.5% and the convergence speed is increased by 21.2% compared with the basic algorithm, which proves that the improved algorithm is notably effective.

An Improved Double Channel Long Short-Term Memory Model for Medical Text Classification - Liang, Shengbin; Chen, Xinan; Ma, Jixin; Du, Wencai; Ma, Huawei (Journal of Healthcare Engineering, 2021)
There are a large number of symptom consultation texts in medical and healthcare Internet communities, and Chinese health segmentation is more complex, which leads to the low accuracy of the existing algorithms for medical text classification. The deep learning model has advantages in extracting abstract features of text effectively. However, for a large number of samples of complex text data, especially for words with ambiguous meanings in the field of Chinese medical diagnosis, the word-level neural network model is insufficient. Therefore, in order to solve the triage and precise treatment of patients, we present an improved Double Channel (DC) mechanism as a significant enhancement to Long Short-Term Memory (LSTM). In this DC mechanism, two channels are used to receive word-level and char-level embedding, respectively, at the same time. Hybrid attention is proposed to combine the current time output with the current time unit state and then using attention to calculate the weight. By calculating the probability distribution of each timestep input data weight, the weight score is obtained, and then weighted summation is performed. At last, the data input by each timestep is subjected to trade-off learning to improve the generalization ability of the model learning. Moreover, we conduct an extensive performance evaluation on two different datasets: cMedQA and Sentiment140. The experimental results show that the DC-LSTM model proposed in this paper has significantly superior accuracy and ROC compared with the basic CNN-LSTM model.

Tourist Sentiment Mining Based on Deep Learning - Li, Weijun; Yang, Qun; Du, Wencai (Artificial Intelligence, 2022)
Mining the sentiment of the user on the internet via the context plays a significant role in uncovering the human emotion and in determining the exactness of the underlying emotion in the context. An increasingly enormous number of user-generated content (UGC) in social media and online travel platforms lead to development of data-driven sentiment analysis (SA), and most extant SA in the domain of tourism is conducted using document-based SA (DBSA). However, DBSA cannot be used to examine what specific aspects need to be improved or disclose the unknown dimensions that affect the overall sentiment like aspect-based SA (ABSA). ABSA requires accurate identification of the aspects and sentiment orientation in the UGC. In this book chapter, we illustrate the contribution of data mining based on deep learning in sentiment and emotion detection.

Exploratory Research on Key Technology of Human-Computer Interactive 2.5-Minute Fast Digital Early Warning for Mild Cognitive Impairment - Li, Nan; Yang, Xiaotong; Du, Wencai; Ogihara, Atsushi; Zhou, Siyu; Ma, Xiaowen; Wang, Yujia; Li, Shuwu; Li, Kai (Computational Intelligence and Neuroscience, 2022)
Objective. As the preclinical stage of Alzheimer’s disease (AD), Mild Cognitive Impairment (MCI) is characterized by hidden onset, which is difficult to detect early. Traditional neuropsychological scales are main tools used for assessing MCI. However, due to its strong subjectivity and the influence of many factors such as subjects’ educational background, language and hearing ability, and time cost, its accuracy as the standard of early screening is low. Therefore, the purpose of this paper is to propose a new key technology of fast digital early warning for MCI based on eye movement objective data analysis. Methodology. Firstly, four exploratory indexes (test durations, correlation degree, lengths of gaze trajectory, and drift rate) of MCI early warning are determined based on the relevant literature research and semistructured expert interview; secondly, the eye movement state is captured based on the eye tracker to realize the data extraction of four exploratory indexes. On this basis, the human-computer interactive 2.5-minute fast digital early warning paradigm for MCI is designed; thirdly, the rationality of the four early warning indexes proposed in this paper and their early warning effectiveness on MCI are verified. Results. Through the small sample test of human-computer interactive 2.5 fast digital early warning paradigm for MCI conducted by 32 elderly people aged 70–90 in a medical institution in Hangzhou, the two indexes of “correlation degree” and “drift rate” with statistical differences are selected. The experiment results show that AUC of this MCI early warning paradigm is 0.824. Conclusion. The key technology of human-computer interactive 2.5 fast digital early warning for MCI proposed in this paper overcomes the limitations of the existing MCI early warning tools, such as low objectification level, high dependence on professional doctors, long test time, requiring high educational level, and so on. The experiment results show that the early warning technology, as a new generation of objective and effective digital early warning tool, can realize 2.5-minute fast and high-precision preliminary screening and early warning for MCI in the elderly.

Data Augmentation for Deep Neural Networks Model in EEG Classification Task: A Review - He, Chao; Liu, Jialu; Zhu, Yuesheng; Du, Wencai (Frontiers in Human Neuroscience, 2021)
Classification of electroencephalogram (EEG) is a key approach to measure the rhythmic oscillations of neural activity, which is one of the core technologies of brain-computer interface systems (BCIs). However, extraction of the features from non-linear and non-stationary EEG signals is still a challenging task in current algorithms. With the development of artificial intelligence, various advanced algorithms have been proposed for signal classification in recent years. Among them, deep neural networks (DNNs) have become the most attractive type of method due to their end-to-end structure and powerful ability of automatic feature extraction. However, it is difficult to collect large-scale datasets in practical applications of BCIs, which may lead to overfitting or weak generalizability of the classifier. To address these issues, a promising technique has been proposed to improve the performance of the decoding model based on data augmentation (DA). In this article, we investigate recent studies and development of various DA strategies for EEG classification based on DNNs. The review consists of three parts: what kind of paradigms of EEG-based on BCIs are used, what types of DA methods are adopted to improve the DNN models, and what kind of accuracy can be obtained. Our survey summarizes the current practices and performance outcomes that aim to promote or guide the deployment of DA to EEG classification in future research and development.

Research on Quality Control of Intelligent Injection Molding System Based on Process Monitoring - Han, Wang; Shasha, Lv; Shaobin, Li; Wencai, Du; Qinggu, Li; Bo, Wang (2021 8th International Conference on Computational Science/Intelligence and Applied Informatics (CSII), 2021)

Malaria Blood Smears Object Detection Based on Convolutional DCGAN and CNN Deep Learning Architectures - Gois, Francisco Nauber Bernardo; Marques, João Alexandre Lobo; De Oliveira Dantas, Allberson Bruno; Santos, Márcio Costa; Neto, José Valdir Santiago; De Macêdo, José Antônio Fernandes; Du, Wencai; Li, Ye (Computer and Information Science, 2023)

Exploring the Current Landscape and Future Directions of Information Technology in Dance Education - Du, Wencai; Chen, Jiao; Xu, Simon (2023 26th ACIS International Winter Conference on Software Engineering, Artificial Intelligence, Networking and Parallel/Distributed Computing (SNPD-Winter), 2023)
Dance education has undergone significant changes with the integration of information technology. Traditional dance pedagogy is now complemented by innovative digital software tools and applications. This work surveys the diverse applications of information technology in dance education at college or university level and the impact it has on teaching and learning processes. We discuss the integration of technology in various aspects of dance education, including skill development, choreography, performance analysis, VR/AR, online virtual learning, and collaborative learning. Additionally, the benefits and challenges associated with the use of information technology are also examined and the future research directions for research and practice in this field are proposed.
Keywords: College and University Education; Dance Education; Education; Federated learning; Humanities; Information Technology; Interactive; Surveys; Technical requirements; Training; Visualization; applications

Noise Detection and Classification in Chagasic ECG Signals Based on One-Dimensional Convolutional Neural Networks - Caldas, Weslley Lioba; Do Vale Madeiro, João Paulo; Pedrosa, Roberto Coury; Gomes, João Paulo Pordeus; Du, Wencai; Marques, João Alexandre Lobo (Computer and Information Science, 2023)

A Machine Learning Approach to Predict the Trend of Obesity Prevalence at a Global Level - Barzinji, Ala Othman; Ma, Chaoying; Du, Wencai; Ma, Jixin (2021 IEEE/ACIS 6th International Conference on Big Data, Cloud Computing, and Data Science (BCD), 2021)